2022
DOI: 10.1002/adsc.202200631
|View full text |Cite
|
Sign up to set email alerts
|

Indenone Synthesis via Transition‐Metal‐Catalyzed Annulation

Abstract: Transition‐metal‐catalyzed annulation reactions to synthesize indenones are reviewed, beginning with the Larock indenone synthesis and focusing on the most recent advances in technology. Proposed reaction mechanisms, and the evidence supporting them, are highlighted throughout this review. Current limitations in these reactions are described in detail. Obtaining high regioselectivity remains challenging with several different classes of alkyne. In particular, high‐yielding and regioselective reactions with alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…16 Initially, application of the same conditions used in the allylation process (Scheme 1) afforded high yields for the reaction between benzoyl silanes and diphenylacetylene to produce an indenone derivative via a desilylative alkenylation/annulation process. Indenones are important scaffolds that have been prepared from a variety of precursors using transition metal catalysis, 17 however this represents the first example of their formation from benzoyl silanes. A brief optimisation was conducted which revealed that (i) Cu(OAc) 2 remained an ideal additive; (ii) AgSbF 6 the optimal silver salt and; (iii) alternative solvents resulted in decreased yields or no reaction.…”
mentioning
confidence: 99%
“…16 Initially, application of the same conditions used in the allylation process (Scheme 1) afforded high yields for the reaction between benzoyl silanes and diphenylacetylene to produce an indenone derivative via a desilylative alkenylation/annulation process. Indenones are important scaffolds that have been prepared from a variety of precursors using transition metal catalysis, 17 however this represents the first example of their formation from benzoyl silanes. A brief optimisation was conducted which revealed that (i) Cu(OAc) 2 remained an ideal additive; (ii) AgSbF 6 the optimal silver salt and; (iii) alternative solvents resulted in decreased yields or no reaction.…”
mentioning
confidence: 99%
“…6 Besides, some radical and other synthetic approaches have also been developed to produce indenone derivatives. 7 In recent years, transition metal catalysis has gained much attention in organic transformations and, to this end, many transition metal based protocols have also been documented in the literature for the synthesis of indenones, 8 which include catalytic annulations of alkynes with ortho-functionalized aromatic aldehydes, esters or nitriles (a & b, Scheme 1). 8b,c However, the use of expensive transition metal catalysts such as Pd and Rh limits their synthetic utility.…”
Section: Introductionmentioning
confidence: 99%
“…Alkyne migratory insertion into a metal–carbon bond is an elementary step in many transition-metal-catalyzed transformations, including alkyne carbozincation, carbomagnesiation, hydroarylation, polymerization, alkynylboration, and carbo- and heteroannulation reactions of alkynes . In many of these examples, alkyne migratory insertion determines the reaction regioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting and controlling the regioselectivity of these reactions has been challenging, however, especially with internal alkynes. Previous synthetic reactions have focused on electronically polarized alkynes, such as alkynones and alkynoates (Scheme a), sterically hindered alkynes, including those with silyl substituents (Scheme b) ,, and alkynes with coordinating directing groups, such as pyridine-containing substrates (Scheme c). ,, …”
Section: Introductionmentioning
confidence: 99%